Mezinárodní trestní tribunál pro bývalou Jugoslávii a sociální rekonstrukce na Balkáně - Muhič Dizdarevič, Selma (Lidé města, 2007)
Armed conflicts in the former Yugoslavia (FY) took place between 1990-1995 and partially as late as 1999. The International Criminal Tribunal for the former Yugoslavia (ICTY, Tribunal) has been established by the United Nations Security Council’s (UN) resolution in May of 1993. It means this Court already existed during the war in Bosnia and Herzegovina (BaH). This article discusses the ICTY’s structure, its contribution to jurisprudence of international humanitarian law and social reconstruction and acceptance of the Court by Bosnian legal experts and public in Serbia. Then, the role of the European Union (EU) in the last Balkan wars and establishment of the protectorate in BaH shall be discussed. I use the term “social reconstruction” primarily in the sense of resurgence of foundations of legal state and free movement of people and information (free movement of goods was already to certain extent reinstated). My aim was to show that establishment of the ICTY and its function represents one of the aspects of paternalistic relationships of international community subjects towards south-eastern Europe, but at the same time such paternalistic attitude is currently the most suitable possible attitude towards communities inhabiting FY which took part in the recent armed conflicts.